1998
DOI: 10.1080/13102818.1998.10818987
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Spotted Wilt Virus on Ornamental Species in Bulgaria

Abstract: This research explores the spread of tomato spotted wilt virus (TSWV) on greenhouse and field grown ornamental species. A total of 152 samples have been examined. The identification of the virus has been conducted with conventional virological methods. The tomato spotted wi It virus has been detected in 25 flower species. Of them, 21 are new hosts for the coun!ly. Physostegia obtusifo/ia (Labiate) is a hitherto new TSWV host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Inspite of the insecticidal, fungicidal, bactericidal, and larvicidal properties of marigold it is also affected by various pathogenic microorganisms such as fungi, viruses and bacteria that cause diseases and damage to the plant which result in yield loss. Up to now, ageratum enation virus [ 15 ], cucumber mosaic virus [ 16 ], papaya ringspot virus [ 17 ], potato virus Y [ 18 ], potato yellow dwarf virus [ 19 ], potato yellow vein virus [ 20 ], tobacco streak virus [ 21 , 22 ], tomato spotted wilt virus [ 23 , 24 , 25 , 26 ] and tomato yellow ring virus [ 27 ] have been reported in marigold plants, causing the symptoms of severe stunting, yellowing, mosaic, leaf curl, crinkle and necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Inspite of the insecticidal, fungicidal, bactericidal, and larvicidal properties of marigold it is also affected by various pathogenic microorganisms such as fungi, viruses and bacteria that cause diseases and damage to the plant which result in yield loss. Up to now, ageratum enation virus [ 15 ], cucumber mosaic virus [ 16 ], papaya ringspot virus [ 17 ], potato virus Y [ 18 ], potato yellow dwarf virus [ 19 ], potato yellow vein virus [ 20 ], tobacco streak virus [ 21 , 22 ], tomato spotted wilt virus [ 23 , 24 , 25 , 26 ] and tomato yellow ring virus [ 27 ] have been reported in marigold plants, causing the symptoms of severe stunting, yellowing, mosaic, leaf curl, crinkle and necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…We collected Z. elegans showing mosaic symptoms from roadside flowerbeds in Chuncheon, Korea. Many viruses including tomato spotted wilt virus (Bakardjieva et al 1998) have been reported to infect Z. elegans. Seven genus-specific primer sets for ilarviruses, potyviruses, fabaviruses, tospoviruses, potexviruses, tobamoviruses and cucumoviruses were used in RT-PCR to detect plant viruses.…”
mentioning
confidence: 99%